Pemanfaatan Teknologi Media Sosial Untuk Pengembangan Karakter Generasi Z Di BBPVP MEDAN - Lusiyanti; Syarifah Fadillah Rezky; Rita Hamdani; Siti Julianita; Meri Sri Wahyuni; Erika Fahmi Ginting; Feri Setiawan (Jurnal Masyarakat Indonesia (Jumas), 2024)
This research focuses on the use of social media technology as a means of developing the character of Generation Z at the Medan Vocational and Productivity Training Center (BBPVP). In this digital era, social media has become an integral part of Generation Z's daily lives, influencing the way they interact, learn and develop. This study aims to explore the potential of social media in forming positive character, improving social skills, and encouraging professional development of trainees at BBPVP Medan. Through qualitative and quantitative approaches, this research analyzes the use of social media platforms such as Instagram, YouTube, and LinkedIn in the context of vocational training. Data was collected through surveys, in-depth interviews, and participant observation of training participants and instructors. The research results show that targeted use of social media can improve soft skills such as digital communication, online collaboration and personal branding. In addition, it was found that the integration of educational content through social media can strengthen the values ​​of work ethics, creativity and lifelong learning among Generation Z. This research also identifies challenges and potential risks, and recommends strategies to maximize the benefits of social media in character development and vocational skills. It is hoped that these findings will provide valuable insights for the development of more effective curriculum and training methods at BBPVP Medan and other vocational training institutions in facing the unique needs of Generation Z in the digital era.